Delayed consultation among pulmonary tuberculosis patients: a cross sectional study of 10 DOTS districts of Ethiopia - Gessessew Amanuel; Walley John D; Newell James N; Mesfin Mengiste M; Madeley Richard J (BMC, 2009)
Abstract Background Delays seeking care increase transmission of pulmonary tuberculosis and hence the burden of tuberculosis, which remains high in developing countries. This study investigates patterns of health seeking behavior and determines risk factors for delayed patient consultation at public health facilities in 10 districts of Ethiopia. Methods New pulmonary TB patients ≥ 15 years old were recruited at 18 diagnostic centres. Patients were asked about their health care seeking behaviour and the time from onset of symptoms to first consultation at a public health facility. First consultation at a public health facility 30 days or longer after onset of symptoms was regarded as prolonged patient delay. Results Interviews were held with 924 pulmonary patients. Of these, 537 (58%) were smear positive and 387 (42%) were smear negative; 413 (45%) were female; 451 (49%) were rural residents; and the median age was 34 years. Prior to their first consultation at a public health facility, patients received treatment from a variety of informal sources: the Orthodox Church, where they were treated with holy water (24%); private practitioners (13%); rural drug vendors (7%); and traditional healers (3%). The overall median patient delay was 30 days (mean = 60 days). Fifty three percent [95% Confidence Intervals (CI) (50%, 56%)] of patients had delayed their first consultation for ≥ 30 days. Patient delay for women was 54%; 95% CI (54%, 58%) and men 51%; 95% CI (47%, 55%). The delay was higher for patients who used informal treatment (median 31 days) than those who did not (15 days). Prolonged patient delay (≥ 30 days) was significantly associated with both patient-related and treatment-related factors. Significant patient-related factors were smear positive pulmonary disease [Adjusted Odds Ratio (AOR) 1.4; 95% CI (1.1 to 1.9)], rural residence [AOR 1.4; 95% CI (1.1 to 1.9)], illiteracy [AOR 1.7; 95% CI (1.2 to 2.4)], and lack of awareness/misperceptions of causes of pulmonary TB. Significant informal treatment-related factors were prior treatment with holy water [AOR 3.5; 95% CI (2.4 to 5)], treatment by private practitioners [AOR 1.7; 95% CI (1.1 to 2.6)] and treatment by drug vendors [AOR 1.9; 95% CI (1.1 to 3.5)]. Conclusion Nearly half of pulmonary tuberculosis patients delayed seeking health care at a public health facility while getting treatment from informal sources. The involvement of religious institutions and private practitioners in early referral of patients with pulmonary symptoms and creating public awareness about tuberculosis could help reduce delays in starting modern treatment.